2016
DOI: 10.33549/physiolres.933007
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic Peptide Resistance of Mesenteric Arteries in Spontaneous Hypertensive Rat Is Alleviated by Exercise

et al.

Abstract: Proximal resistance vessels, such as the mesenteric arteries, contribute substantially to the peripheral resistance. The reactivity of resistance vessels to vasoactive substance like natriuretic peptides plays an important role in the regulation of blood pressure. In current study, we investigated the reactivity of mesenteric arteries to atrial natriuretic peptide (ANP), a well known vasodilating factor, in spontaneously hypertensive rats (SHR), as well as the effects of exercise training on it. As a result, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Apart from the rarity of studies on the effect of RT on ANP levels in hypertensive patients, Yu et al showed that 12 weeks of swimming without load reversed the vascular resistance to ANP in SHR and pronounced the vasorelaxant effects of ANP. DBP, SBP and MAP also showed significant reductions 50 . In the only study of the effect of saffron on ANP, the authors found that crocetin in hypertrophy induced by blocking the MEK‐ERK1/2 signalling pathway prevented ANP from increasing and has a protective impact on the progression of cardiac failure 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the rarity of studies on the effect of RT on ANP levels in hypertensive patients, Yu et al showed that 12 weeks of swimming without load reversed the vascular resistance to ANP in SHR and pronounced the vasorelaxant effects of ANP. DBP, SBP and MAP also showed significant reductions 50 . In the only study of the effect of saffron on ANP, the authors found that crocetin in hypertrophy induced by blocking the MEK‐ERK1/2 signalling pathway prevented ANP from increasing and has a protective impact on the progression of cardiac failure 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Next, a spontaneously hypertensive rat (SHR) model was used to assess the chronic effect of PFHE on the cardiovascular system. This in vivo model is considered similar to the essential pathophysiology of hypertension [21].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, this is in line with the lack of difference between groups concerning intracellular cGMP content in thoracic aorta observed in our experimental conditions. It is widely documented that resistant arteries play an important role in the regulation of blood pressure in SHR (Yu et al, 2016) and are less dependent on NO than thoracic aorta (Lyoussi et al, 2018). A complementary study of the vascular reactivity in resistance arteries would therefore be interesting to better assess the effects of CD and BAY 41-2272 treatment.…”
Section: Discussionmentioning
confidence: 99%